From Blank Space to the Appropriation of Public Space - Jorge Javier (The International Journal of Architectonic, Spatial, and Environmental Design, 2026)
The experience of public space originates from two fundamental activities: being and walking. Living and inhabiting these open spaces nourishes our senses, which are enriched by our experiences as we move through them. We are constantly bombarded by visual stimuli, from billboards to screens and lights, by the noise of the world and the sounds of nature, and by the myriad smells and flavors that mingle in the air—a cocktail of sensations that invade our minds, enabling us to identify the public spaces we traverse based on these distinctive characteristics, creating a series of voids in cities that help us understand the urban environment. This sensory manifestation intertwines with our personal experiences and influences our mood, whether through memory, nostalgia, or the recollection of a previous visit. We construct a “space” through experiences, which allow us to better understand our intentions for alteration, improvement, or intervention. As a living space, we believe that the inevitable evolution of tectonic media provides a guideline for leaving a mark on our transcendence as users. The interaction of public space with the people who inhabit it forms the basis of the meaning it can hold, generating a sense of belonging and social relevance in its immediate surroundings. An uninhabited space becomes irrelevant, sterile, and meaningless, incapable of conveying its purpose and significance in a city setting through its own form.